Epigenetics Underlying Susceptibility and Resilience Relating to Daily Life Stress, Work Stress, and Socioeconomic Status - Gottschalk, Michael G.; Domschke, Katharina; Schiele, Miriam A. (Frontiers in Psychiatry, 2020)
Susceptibility and resilience to mental disorders result from a complex choreography of gene-environment interactions (G×E) with epigenetics at the intersection of external psychological stressors and internal biological systems. Increasing awareness of the growing disease burden influenced by daily life stress (‘daily hassles’), work-related stress and low socioeconomic status has resulted in a novel interest into their underlying molecular signatures. This review offers a brief outline of psychiatric epigenetics and a comprehensive overview of recent findings exploring the relationship of various occupational stressors and DNA methylation in epigenome-wide association studies (EWAS) and in candidate gene studies including the serotonin transporter (SLC6A4; 5-HTTLPR), melatonin receptor 1A (MTNR1A), brain-derived neurotrophic factor (BDNF), tyrosine hydroxylase (TH) and the protein family of DNA methyltransferases (DNMT). Conceptual and methodological challenges of epigenetic investigations with a special focus on G×E are highlighted and discussed. The findings are integrated into a pathophysiological framework featuring epigenetic plasticity factors and work-related stress as a possible central detrimental component targetable by workplace interventions. Finally, the potential of dynamic epigenetic biomarkers of treatment response to pharmacotherapy or psychotherapy is expanded upon.